Hydrothermal activity fuels microbial sulfate reduction in deep and distal marine settings along the Arctic Mid Ocean Ridges - Desiree L. Roerdink; Francesca Vulcano; Jan-Kristoffer Landro; Karen E. Moltubakk; Hannah R. Babel; Steffen Leth Jørgensen; Tamara Baumberger; Ingeborg E. Økland; Eoghan P. Reeves; Ingunn H. Thorseth; Laila J. Reigstad; Harald Strauss; et al. (Frontiers in Marine Science, 2024)
Microbial sulfate reduction is generally limited in the deep sea compared to shallower marine environments, but cold seeps and hydrothermal systems are considered an exception. Here, we report sulfate reduction rates and geochemical data from marine sediments and hydrothermal vent fields along the Arctic Mid Ocean Ridges (AMOR), to assess the significance of basalt-hosted hydrothermal activity on sulfate reduction in a distal deep marine setting. We find that cored marine sediments do not display evidence for sulfate reduction, apart from low rates in sediments from the Knipovich Ridge. This likely reflects the overall limited availability of reactive organic matter and low sedimentation rates along the AMOR, except for areas in the vicinity of Svalbard and Bear Island. In contrast, hydrothermal samples from the Seven Sisters, Jan Mayen and Loki’s Castle vent fields all demonstrate active microbial sulfate reduction. Rates increase from a few 10s to 100s of pmol SO 4 2- cm -3 d -1 in active high-temperature hydrothermal chimneys, to 10s of nmol SO 4 2- cm -3 d -1 in low-temperature barite chimneys and up to 110 nmol cm -3 d -1 in diffuse venting hydrothermal sediments in the Barite field at Loki’s Castle. Pore fluid and sediment geochemical data suggest that these high rates are sustained by organic compounds from microbial mats and vent fauna as well as methane supplied by high-temperature hydrothermal fluids. However, significant variation was observed between replicate hydrothermal samples and observation of high rates in seemingly inactive barite chimneys suggests that other electron donors may be important as well. Sediment sulfur isotope signatures concur with measured rates in the Barite field and indicate that microbial sulfate reduction has occurred in the hydrothermal sediments since the recent geological past. Our findings indicate that basalt-hosted vent fields provide sufficient electron donors to support microbial sulfate reduction in high- and low-temperature hydrothermal areas in settings that otherwise show very low sulfate reduction rates.

An Arctic natural oil seep investigated from space to the seafloor - Giuliana Panieri; Claudio Argentino; Sofia P. Ramalho; Francesca Vulcano; Alessandra Savini; Luca Fallati; Trond Brekke; Giulia Galimberti; Federica Riva; João Balsa; Mari H. Eilertsen; Runar Stokke; et al. (Science of The Total Environment, 2024)

Hot Vents Beneath an Icy Ocean: The Aurora Vent Field, Gakkel Ridge, Revealed - Eva Ramirez-Llodra; Claudio Argentino; Maria Baker; Antje Boetius; Carolina Costa; Håkon Dahle; Emily Denny; Pierre-Antoine Dessandier; Mari Eilertsen; Benedicte Ferre; Christopher German; Kevin Hand; et al. (Oceanography, 2023)
Evidence of hydrothermal venting on the ultra-slow spreading Gakkel Ridge in the Central Arctic Ocean has been available since 2001, with first visual evidence of black smokers on the Aurora Vent Field obtained in 2014. But it was not until 2021 that the first ever remotely operated vehicle (ROV) dives to hydrothermal vents under permanent ice cover in the Arctic were conducted, enabling the collection of vent fluids, rocks, microbes, and fauna. In this paper, we present the methods employed for deep-sea ROV operations under drifting ice. We also provide the first description of the Aurora Vent Field, which includes three actively venting black smokers and diffuse flow on the Aurora mound at ~3,888 m depth on the southern part of the Gakkel Ridge (82.5°N). The biological communities are dominated by a new species of cocculinid limpet, two small gastropods, and a melitid amphipod. The ongoing analyses of Aurora Vent Field samples will contribute to positioning the Gakkel Ridge hydrothermal vents in the global biogeographic puzzle of hydrothermal vents.